Correlation between stages of breast cancer and BMI in females: a multi-centre study - Noureen, Aqdus; Javed, Ayesha; Siddiqui, Riaz Hussain; Shakir, Fatima Tuz Zahra (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the link between breast cancer and obesity in women by using body mass index at the time of diagnosis. Method: The cross-sectional study was conducted from October 2019 to April 2020 at Pakistan Ordinance Factories Hospital, Wah Cantt, and Islamabad Medical Complex National Engineering and Scientific Commission Hospital, Islamabad, Pakistan. The sample comprised women aged 40-70 years with a recent diagnosis of breast cancer. Patients' body mass index values were calculated after they were diagnosed and additional staging examinations were carried out. Data was analysed using SPSS 21. Results: There were 100 cases with a mean age of 52.24±7.47 years. There was a significant link between obesity and breast cancer (p=0.002), with higher body mass index carrying a higher risk of advanced breast cancer. Conclusion: Obesity may contribute to postmenopausal breast cancer in women. Key Words: Breast cancer, Obesity, BMI.